How I became a qualitative researcher? - Scârneci, Florentina (Sociologija. Mintis ir veiksmas, 2012)
Abstract: The present article presents the personal experience of the author with research methodologies.Some limits of the social scientific research are being analyzed, regarding two of the stages of research:theoretical framework and operationalization; this is the way in which the validity of the criteria and theconstruct validity came into discussion. At the same time, the character of sociological theories and theirutility in scientific research are under discussion. Reasons for which qualitative is chosen are listed despitethe constant disapproval of this method in Romanian sociology (and it’s marginalization in Central – EastEurope). The advantages of qualitative research in socio-human sciences are presented (what is being researched,through what methods, with what results). The special case of using the focus-group at a large scaleis being analyzed (its use without following two of the major qualitative principals: theoretical samplingand theoretical saturation). The article advocates for the usage of qualitative and it is written in a personaland provocative style.Key words: sociological research methodology, qualitative research, quantitative research, validity.SANTRAUKAKODĖL AŠ PASIRINKAU KOKYBINIO TYRIMO BŪDĄ?Straipsnis parengtas remiantis asmenišku autorės, dirbančios tyrimo metodologijų srityje, patyrimu.Analizuojami sociologinio mokslinio tyrimo trūkumai, susiję su dviem tyrimo pakopomis: teorine struktūrair operacionalizacija. Viena vertus, svarbu kriterijų ir konstrukcijų pagrįstumas, kita vertus, sociologiniųteorijų taikymo moksliniams tyrimams patikimumas. Aptariamos kokybinio metodo pasirinkimo priežastysir aplinkybės, rodančios, kad šis metodas Rumunijoje ir Centrinėje Rytų Europoje yra marginalizuojamas.Svarstomi įvairūs kokybinio metodo privalumai, įskaitant plačios apimties focus-grupių pavyzdžius. Straipsnioautorė nevengia kokybinio tyrimo būdo apologijos provokacinio stiliaus.